2004
DOI: 10.3141/1894-25
|View full text |Cite
|
Sign up to set email alerts
|

Home-Based Teleshoppers and Shopping Travel: Do Teleshoppers Travel Less?

Abstract: Some have assumed that teleshopping will become a functional substitute for traditional retail shopping and thereby reduce physical shopping trips and vehicle miles traveled. More recent studies have painted a far more complex picture, in which a combination of lifestyle, shopping opportunities, and the costs of travel all play a role in a person's choice of shopping modes. In this study, data from an activity-diary survey collected by the Metropolitan Transportation Commission, California, were analyzed to ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 10 publications
1
43
1
Order By: Relevance
“…Ferrell (2004) found that teleshoppers chain their shopping trips more often than non-teleshoppers, although no such effect was found in his second study (Ferrell, 2005). He remarks that both teleshopping and trip chaining could be used as 'travel-efficiency tools'.…”
Section: Theoretical Frameworkmentioning
confidence: 95%
See 2 more Smart Citations
“…Ferrell (2004) found that teleshoppers chain their shopping trips more often than non-teleshoppers, although no such effect was found in his second study (Ferrell, 2005). He remarks that both teleshopping and trip chaining could be used as 'travel-efficiency tools'.…”
Section: Theoretical Frameworkmentioning
confidence: 95%
“…Ferrell (2004Ferrell ( , 2005 has analysed activity diaries using multivariate analysis techniques to investigate the relationship between teleshopping (i.e.,…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter, weekend shopping, is defined as the percentage of in-store shopping activities conducted at weekends out of all in-store shopping activities. Other dimensions of activity travel behavior, such as leisure activity frequency and shopping trip chaining, were considered as in previous literature, to allow the comparison of our results with those of previous studies (Ferrell 2004;Farag et al 2007). Leisure activity frequency is the number of leisure activities conducted during the survey week.…”
Section: Variablesmentioning
confidence: 97%
“…For instance, Ferrell (2004) examined the impact of teleshopping on out-ofhome shopping trips and travel distance. The results suggested that home shopping tends to increase shopping trips and the number of chained shopping trips with a reduction in the total travel distance.…”
mentioning
confidence: 99%